2010
DOI: 10.1177/0960327110388539
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases in carbon monoxide poisoning patients

Abstract: Objective: Carbon monoxide poisoning (COP) is one of the important causes of morbidity and mortality in toxicological cases. In this study, we aimed to find out more about the pathophysiology of COP by investigating the effects of COP on oxidative stress parameters such as total oxidant status (TOS) and total antioxidant status (TAS). Methods: Eighty-eight patients admitted to the emergency department of our hospital with acute COP and 35 healthy adults as control group were included in this study. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 13 publications
(12 reference statements)
3
34
3
1
Order By: Relevance
“…The result of the study concur with Ismail et al, [15] and Patel et al, [35] which reported a decrease in concentration of SOD in comparison to the control with a significant negative correlation with COHb level. However, the result disagreed with the findings of Thom et al, [31]; Webber et al, [36]; Piantaosi et al, [37]; Hamed et al, [38] and Kavakli et al, [13]. The Pearson correlational study also showed a linear relationship between acute grades of CO and vitreous SOD ( Figure. 2).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The result of the study concur with Ismail et al, [15] and Patel et al, [35] which reported a decrease in concentration of SOD in comparison to the control with a significant negative correlation with COHb level. However, the result disagreed with the findings of Thom et al, [31]; Webber et al, [36]; Piantaosi et al, [37]; Hamed et al, [38] and Kavakli et al, [13]. The Pearson correlational study also showed a linear relationship between acute grades of CO and vitreous SOD ( Figure. 2).…”
Section: Discussioncontrasting
confidence: 55%
“…In carbon monoxide poisoned patients, an altered balance between reactive oxygen species and antioxidant levels has been reported [13]. Also it has been observed that free radicals and oxidative stress are among factors involved in pathogenesis of acute carbon monoxide poisoning and particularly appear to have a role in carbon monoxide induced cardio-toxicity [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, they measured, in patients with CO poisoning (n ¼ 88) and control subjects (n ¼ 37), serum levels of total oxidant and antioxidant status and calculated oxidative stress index (¼ total oxidant status/total antioxidant status). 1 They found that total oxidant status and oxidative stress index, but not total antioxidant status significantly increased in patients with CO poisoning when compared with controls. Additionally, they found that carboxyhemoglobin (COHb), total oxidant status and oxidative stress index were significantly reduced after 6 h of treatment.…”
mentioning
confidence: 99%
“…1 Although lipid peroxidation has been linked to CO-induced neuropathology for more than two decades, 2 serum levels of oxidative stress markers have not been investigated before. In this study, they measured, in patients with CO poisoning (n ¼ 88) and control subjects (n ¼ 37), serum levels of total oxidant and antioxidant status and calculated oxidative stress index (¼ total oxidant status/total antioxidant status).…”
mentioning
confidence: 99%
“…Apart from activation of nitric oxide and release of other free radicals in carbon monoxide poisoning, the other contributory factors for thrombus formation are mitochondrial dysfunction, microvascular impairment, and oxidative stress and leads to endothelial damage that subsequently increases thrombin formation as evidenced by enhanced tissue factor expression. 6 It is likely that oxidative stress might have contributed to the activation of the coagulation cascade.…”
mentioning
confidence: 99%